Genetic Influences on Brain Gene Expression in Rats Selected for Tameness and Aggression. Issue 3 (3rd September 2014) - Heyne, Henrike O; Lautenschläger, Susann; Nelson, Ronald; Besnier, François; Rotival, Maxime; Cagan, Alexander; Kozhemyakina, Rimma; Plyusnina, Irina Z; Trut, Lyudmila; Carlborg, Örjan; Petretto, Enrico; Kruglyak, Leonid; et al.
Abstract: Interindividual differences in many behaviors are partly due to genetic differences, but the identification of the genes and variants that influence behavior remains challenging. Here, we studied an F2 intercross of two outbred lines of rats selected for tame and aggressive behavior toward humans for >64 generations. By using a mapping approach that is able to identify genetic loci segregating within the lines, we identified four times more loci influencing tameness and aggression than by an approach that assumes fixation of causative alleles, suggesting that many causative loci were not driven to fixation by the selection. We used RNA sequencing in 150 F2 animals to identify hundreds of loci that influence brain gene expression. Several of these loci colocalize with tameness loci and may reflect the same genetic variants. Through analyses of correlations between allele effects on behavior and gene expression, differential expression between the tame and aggressive rat selection lines, and correlations between gene expression and tameness in F2 animals, we identify the genes Gltscr2, Lgi4, Zfp40, and Slc17a7 as candidate contributors to the strikingly different behavior of the tame and aggressive animals.